Hybrid procedure of bilateral pulmonary artery banding and bilateral ductal stenting in an infant with aortic atresia and interrupted aortic arch. Issue 7 (25th February 2014) - Kobayashi, Daisuke; Turner, Daniel R.; Delius, Ralph E.; Aggarwal, Sanjeev
<x xml:space="preserve">Abstract</x> We report an infant with aortic valve atresia, interrupted aortic arch, ventricular septal defect, confluent pulmonary arteries, bilateral arterial ducts, absent common carotid arteries, and anomalous coronary arteries arising from main pulmonary artery. Hybrid procedure consisting of bilateral pulmonary artery banding and bilateral arterial duct stenting was performed at 4 weeks of age. Hybrid procedure can be an alternative palliative approach in an infant with this complex cardiac anatomy. © 2014 Wiley Periodicals, Inc.